Correction to: Subacute thyroiditis during early pregnancy: a case report and literature review - Chao-Fang Bai; Guang-Hui Shen; Ying Yang; Ke Yang; Melvin R. Hayden; Yuan-Yuan Zhou; Xing-Qian Geng (BMC, 2022)
An amendment to this paper has been published and can be accessed via the original article.